Polysilicon Encapsulation Gettering with Electric-Field-Enhanced Isothermal Annealing for Copper Impurities in Bulk Silicon - Lee, W. P.; Teh, E. P.; Yow, H. K.; Choong, C. L.; Tou, T. Y. (2004)
A metal gettering strategy for copper in silicon, combining polysilicon encapsulation, isothermal annealing, and an external dc electric field is proposed. Experimental results have shown faster gettering of copper at the polysilicon layer to a higher concentration level above the copper detection limits of total reflection X-ray florescence spectroscopy. The improvement in the observed gettering efficiency is attributed to the directional drift-diffusion of copper interstitials to the effective polysilicon gettering sites, under the influence of the applied potential gradient and the thermally induced gettering concentration gradient, respectively, providing a simple and effective method for minimizing and monitoring of Cu content in bulk silicon wafers. (C) 2004 The Electrochemical Society.